A Study of HbA1c, fasting and 2 hour plasma glucose levels in current smokers presenting at a tertiary care hospital in North India - Verma, Niket (International Journal of Advances in Medicine, 2018)
Background: There is a concern that smokers are at increased risk of diabetes and this association has received surprisingly little attention. This study aims to study the relationship of smoking with three glycaemic variables (HbA1c, fasting and 2 hour post prandial plasma glucose levels) in current smokers and describe the potential impact of smoking in the context of screening for diabetes by using one of these glycaemic variables. Methods: 150 patients attending the OPD of Santosh Medical College were part of this Cross sectional population based study. One hundred were smokers and fifty non-smokers and non-diabetics. All participants were subjected to fasting plasma glucose level, 2 hour plasma glucose level and HbA1c testing. Results: Mean values of all three variables are substantially higher in smokers as compared to non-smokers. HbA1c levels show an increasing trend with increasing age among both groups. Mean plasma glucose levels show increasing values with increasing age but the trend is not uniform. Among females, only HbA1c levels whereas among males all three variables show a strong correlation with smoking. No correlation was observed between the number of cigarettes smoked daily or smoking index and the glycaemic variables. All variables show an increasing trend as the number of years of smoking increases. Conclusions: A higher prevalence of diabetes is seen in current smokers when we consider HbA1c levels indicating the beneficial effect of using HbA1c levels for identifying current smokers at risk of diabetes mellitus.